Unimolecular decomposition kinetics of the stabilised Criegee intermediates CH2OO and CD2OO. Issue 38 (21st September 2018) - Stone, Daniel; Au, Kendrew; Sime, Samantha; Medeiros, Diogo J.; Blitz, Mark; Seakins, Paul W.; Decker, Zachary; Sheps, Leonid
Abstract : Decomposition kinetics of stabilised CH2 OO and CD2 OO Criegee intermediates have been investigated as a function of temperature (450–650 K) and pressure (2–350 Torr) using flash photolysis coupled with time-resolved cavity-enhanced broadband UV absorption spectroscopy. Abstract : Decomposition kinetics of stabilised CH2 OO and CD2 OO Criegee intermediates have been investigated as a function of temperature (450–650 K) and pressure (2–350 Torr) using flash photolysis coupled with time-resolved cavity-enhanced broadband UV absorption spectroscopy. Decomposition of CD2 OO was observed to be faster than CH2 OO under equivalent conditions. Production of OH radicals following CH2 OO decomposition was also monitored using flash photolysis with laser-induced fluorescence (LIF), with results indicating direct production of OH in the v = 0 and v = 1 states in low yields. Master equation calculations performed using the Master Equation Solver for Multi-Energy well Reactions (MESMER) enabled fitting of the barriers for the decomposition of CH2 OO and CD2 OO to the experimental data. Parameterisations of the decomposition rate coefficients, calculated by MESMER, are provided for use in atmospheric models and implications of the results are discussed. For CH2 OO, the MESMER fits require an increase in the calculated barrier height from 78.2 kJ mol −1 to 81.8 kJ mol −1 using a temperature-dependent exponential down model for collisional energy transfer with 〈Δ E 〉down = 32.6( T /298 K) 1.7 cm −1 in He. The low- and high-pressure limit rate coefficients are k 1, 0 = 3.2 × 10 −4 ( T /298) −5.81 exp(−12 770/ T ) cm 3 s −1 and k 1, ∞ = 1.4 × 10 13 ( T /298) 0.06 exp(−10 010/ T ) s −1, with median uncertainty of ∼12% over the range of experimental conditions used here. Extrapolation to atmospheric conditions yields k 1 (298 K, 760 Torr) = 1.1+1.5−1.1 × 10 −3 s −1 . For CD2 OO, MESMER calculations result in 〈Δ E 〉down = 39.6( T /298 K) 1.3 cm −1 in He and a small decrease in the calculated barrier to decomposition from 81.0 kJ mol −1 to 80.1 kJ mol −1 . The fitted rate coefficients for CD2 OO are k 2, 0 = 5.2 × 10 −5 ( T /298) −5.28 exp(−11 610/ T ) cm 3 s −1 and k 2, ∞ = 1.2 × 10 13 ( T /298) 0.06 exp(−9800/ T ) s −1, with overall error of ∼6% over the present range of temperature and pressure. The extrapolated k 2 (298 K, 760 Torr) = 5.5+9.2−5.5 × 10 −3 s −1 . The master equation calculations for CH2 OO indicate decomposition yields of 63.7% for H2 + CO2, 36.0% for H2 O + CO and 0.3% for OH + HCO with no significant dependence on temperature between 400 and 1200 K or pressure between 1 and 3000 Torr.